Managerial processes: business process that sustain performance - FIRAT, SENİYE ÜMİT (EMERALD GROUP PUBLISHING LTD, 2011)
Purpose - It is argued that whilst operational and support processes deliver performance presently, it is the managerial processes that sustain performance over time. The purpose of this research paper is to better understand what these managerial processes are and how they influence organisational performance. Design/methodology/approach - The theoretical background is reviewed covering literature on the subject of business process management, resourced-based view (RBV), dynamic capabilities and managerial processes. A research framework leads to qualitative case study-based research design. Data are collected from 37 organisations across Europe, classified according to their performance. Findings - Findings suggest that the five managerial processes and their constituent managerial activities, identified through the empirical research, influence performance of organisations as an interconnected managerial system rather than as individual processes and activities. Also, the execution and maturity of this managerial system is influenced by the perceptions of the managers who organise it. Research limitations/implications - Within the limitation of the study the discussion leads to eight research propositions that contribute to our understanding of how managerial processes influence organisational performance. These propositions and ensuing discussion provide insights into the content and structure of managerial processes, as well as contributing to the debate on RBV by suggesting that managerial processes and activities could be considered as valuable, rare and inimitable resources. Furthermore, the discussion on how managerial perceptions influence the organisation and execution of the managerial system contributes towards our understanding of how and why dynamic capabilities develop. Practical implications - The results suggest that in higher performing organisations, managers: demonstrate a wider awareness of the overall managerial system; achieve a balance between short-term and future-oriented activities; exploit their managerial activities for multiple purposes; demonstrate greater maturity of managerial activities; and pay greater attention to the organisation of the managerial system. Originality/value - This paper presents one of the first empirical studies that attempt to understand how business processes, and particularly managerial processes, as an interconnected managerial system serve to sustain performance of organisations.
Keywords: Organizational performance; Management strategy; RESOURCE-BASED VIEW; DYNAMIC CAPABILITIES; PROCESS MANAGEMENT; ORGANIZATIONAL PERFORMANCE; STRATEGY PROCESS; KNOWLEDGE; FIRM; TRANSFORMATION; EXPLOITATION; EXPLORATION